EXPLORING EXCELLENCE IN MEDIA EDUCATION: DEPARTMENT OF MASS COMMUNICATION, AUCHI POLYTECHNIC - Adebayo, Michael Oluwadare (International Journal of Contemporary Research in Marketing and Management Sciences, 2025)
Artificial intelligence (AI), defined as the simulation of human intelligence by machines, enables automated data analysis, personalized marketing, and enhanced consumer interactions. This study explores the integration and effects of AI in advertising, revealing that while advertisers increasingly leverage AI technologies for efficiency and effectiveness, consumer awareness of AI's role remains limited and fragmented. This review was anchored on Technological Determinism theory. The research, using secondary data, highlights AI's capability to tailor advertisements, predict consumer behavior, and improve engagement through tools like chatbots and virtual assistants. Despite privacy concerns, AI's precise targeting and personalized content are revolutionizing advertising strategies, driving innovation and satisfaction. The study emphasizes the need for a comprehensive understanding of AI's applications and effects, suggesting that AI is a primary driver of change in advertising, influencing consumer behavior and industry practices. The ongoing evolution of AI technology is expected to further advance advertising techniques, reinforcing its role as a critical force in the digital age.